SYNTHESIS OF CHAINED-ELLIPTIC FUNCTION WAVEGUIDE BANDPASS FILTER WITH HIGH REJECTION - NG GUAN, SHEN (2021)
This thesis presents the synthesis of a bandpass filter to achieve high selectivity and rejection properties using a new class of filter functions called chained-elliptic function filters. Chained-elliptic filters have higher selectivity compared to Chebyshev function filters and have the property of sensitivity to manufacturing tolerance reduction in chained-function filters. The proposed design has high selectivity and reduced sensitivity, enabling easier and faster filter fabrication, which greatly reduces the time and cost required to manufacture a millimeter-wave filter. The characteristic polynomials of chained-elliptic function filters are derived (through chaining elliptic filtering function) and extracted to form the coupling matrix of the bandpass filter.